(3OhQ GdLGeYGJ GdCgdjI ai eYGdLI eTcdGJ GdJYdje GdLGeYi HeUQ (B: s (3JUhQ ebJQM (B/ s - (3NGdO eMeO CMeO eMeO SjO CMeOs; (3YHOGddWja eMehO eMeO (B: s ((3GdbGgQI (B: s (3NGdO eMeO CMeO eMeO SjO CMeO (B: s, 2020)
(3gOa GdHMK GdMGdi Gdi hVY JUhQ dLGeYI CgdjI eUQjI JYGdL eTcdGJ GdJYdje GdLGeYi h Je Pdc ef NdGd MOhO GdHMK(B: (3MOhO ehVhYjI(B: (3JbJUQ GdOQGSI Ydi hGbY GdLGeYGJ GdCgdjI h GdMchejI ai GdeLJeY GdeUQi(B. (3MOhO RefjI(B: (3gPG GdHMK jbOe JUhQ ebJQM ddaJQI GdRefjI (B(2020-2030) (3dOhQ GdLGeYGJ GdCgdjI ai NOeI GdeLJeY GdeUQis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdOhd GdYQHjI (B- (3GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe (B- (3eYgO GdHMhK h GdOQGSGJ GdYQHjI (B- (3bSe HMhK h OQGSGJ GdJQHjIs
Keywords: (3GdJYdje GdLGeYi s; (3GdLGeYI GdCgdjI s; (3eUQs